Bubrežni tumori u detinjstvu - pregledni članak - Vujanić, Gordan M; Đuričić, Slaviša M (Scripta Medica, 2022)
Renal tumours of childhood are rare, although they are one of the most commonsolid tumours in children. They include numerous entities, which have differentclinical, histological, molecular biological and prognostic features, so their precisediagnosis and staging are critical for appropriate treatment. The most commonis Wilms’ tumour (WT) with ~80-85 % of all cases, whereas other entitiesincluding mesoblastic nephroma, clear cell sarcoma, rhabdoid tumour, renalcell carcinoma, metanephric tumours and others are very rare (2-4 % each)which explains why they represent a big diagnostic challenge for diagnostic pathologists.They are subclassified into three risk groups – low, intermediate andhigh – which have different treatments and prognosis. There are two big studygroups which have different approaches but remarkable similar outcomes. TheInternational Society of Paediatric Oncology approach (followed in most of theworld) is based on preoperative chemotherapy, followed by surgery and furthertherapy, whereas the Children’s Oncology Group approach (followed mainly inthe United States and Canada) is based on primary surgery, followed by postoperativetreatment.
Keywords: Tumori bubrega; Wilmsov tumor; Prognostičke grupe; Kliničko-patološki oblici